Sorghum, millet and cassava as alternative dietary energy sources for sustainable quail production – A review - Mnisi, Caven Mguvane; Oyeagu, Chika Ethelbert; Akuru, Eunice Amaka; Ruzvidzo, Oziniel; Lewu, Francis Bayo (Frontiers in Animal Science, 2023)
Diversification and expansion of the poultry industry with fast-growing and highly prolific birds such as the quail (Coturnix coturnix), could contribute significantly in achieving global food and nutrition security. However, sustainable intensification of the quail relies on the cost of dietary ingredients used during feed formulations. The use of non-conventional energy sources such as sorghum, millet, and cassava in lieu of expensive energy sources such as maize, could ensure sustainable quail businesses. Generally, alternative feedstuffs should be cost-effective and possess comparable nutritional qualities as maize. In tropical countries such as South Africa, the use of sorghum, millet, and cassava in quail diets can serve as ideal alternatives because they have relatively comparable energy values as maize. Furthermore, these alternatives are largely available and easily accessible in many farming areas of South Africa. However, the presence of antinutritional factors such as tannins, cyanides and phytic acid, among others, as well as their high fiber levels may limit their utilization in quail nutrition. Nevertheless, attempts have been made to develop improved varieties with low antinutrient compositions, for instance, low-tannin sorghum varieties are increasingly being fed to poultry birds. Furthermore, there is growing evidence that certain processing techniques such as sun-drying, soaking, boiling and fermentation, among others, can lower the concentrations of antinutrients in these alternative feedstuffs, thus increasing their feeding value. To this end, nutritional feeding trials on the positive effects of sorghum, millet and cassava in quail nutrition are inconsistent, mainly due to differences in cultivar type, harvesting site or environmental conditions, sampling, and handling methods amongst other factors. Thus, the present review aimed to discuss the potential of substituting maize with sorghum, millet, and cassava in quail diets.